Role of Diffusion-Weighted Imaging in the Evaluation of Perianal Fistulae - Boruah, Deb K.; Hazarika, Karuna; Ahmed, Halimuddin; Borah, Krishna K.; Borah, Samudra; Malakar, Seema; Hajoari, Nobojit (Indian Journal of Radiology and Imaging, 2021)
Background Magnetic resonance imaging (MRI) is the imaging modality of choice for evaluating perianal fistulae, due to its ability to show the relationship of perianal fistulae with anal sphincters, fistula extensions, secondary ramifications and associated complications.Aim To evaluate the role of diffusion-weighted MRI in the evaluation of perianal fistulae.Settings and Design A hospital-based cross-sectional study.Materials and Methods The study group composed of 47 patients of perianal fistula. MRI with diffusion-weighted imaging (DWI) was performed with Philips 0.5 T Ingenia scanner. DWI with different b-values (b = 50, b = 400, and b = 800 smm2) were obtained. The MRI findings were correlated with local clinical examination and or surgical findings.Statistical Analysis Used Chi-square test, independent samples t-test, and receiver operating characteristic curve analysis.Result Fifty-nine perianal fistulas in 47 patients were included in the study sample. The visibility of perianal fistula on DWI was less than T2-weighted (T2W) and combined DWI-T2W images. Distinctly visualized (visibility score 2) perianal fistulas were observed in 47 fistulas (79.6%) on DWI, 54 (91.5%) on T2W, and 58 (98.3%) on DWI-T2W images. The mean of apparent diffusion coefficient (ADC) values of active fistula was 0.972 ± 0.127 [SD] 10−3 mm2/s and inactive was 1.232 ± 0.185 [SD] 10−3 mm2/s with a significant difference (p-value < 0.0005). A cut-off mean ADC value of 1.105 × 10−3 mm2/s was used to differentiate active from the inactive fistula with a sensitivity of 87.5% and specificity of 73.3%.Conclusion Combined DWI-T2W evaluation had a better performance in the detection of fistula than DWI or T2W alone. DWI with mean ADC calculation had a good performance in differentiating active from the inactive fistulas.
Keywords: intersphincteric; magnetic resonance imaging; perianal fistulae; transsphincteric